Continuous Renal Replacement Therapy: A Practical Guide - Zaheer Amin Virani; Chaitrali Gawde (Indian Journal of Kidney Diseases)
Continuous renal replacement therapy (CRRT) is a vital cog in the management of critically ill patients. Its slow, continuous nature gives the clinician the leeway to dose medications and nutrition with more confidence while keeping the patient in a euvolemic state. Both diffusive and convective clearance can be provided depending on the indication. This article will enumerate the indications, dosage, complications and trouble shooting aspects of CRRT.